2020
DOI: 10.5530/ijmedph.2020.3.20
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Faced by ASHAs during their Field Works: A Cross Sectional Observational Study in Rural Area of Jaipur, Rajasthan

Abstract: Introduction: ASHA, the grass root level worker is a bridge between population and health system. Objectives: To determine the challenges and hurdles faced by ASHA during their field work in rural area of district Jaipur, Rajasthan. Methods and Materials: A field based descriptive, observational study was conducted among 135 ASHA's of ten PHC's of two blocks of Jaipur, Rajasthan from September 2018 to April 2019 by using a pretested, semi structured questionnaire for socioeconomic profile of ASHA and in-depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Similar finding were reported by others studies also (6,11,14). All the ASHAs of current study stated that they do not find adequate time to complete existing work because in addition to their own assigned work, ANM pressurize them to fulfil some of their services targets (15). This makes them over loaded.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar finding were reported by others studies also (6,11,14). All the ASHAs of current study stated that they do not find adequate time to complete existing work because in addition to their own assigned work, ANM pressurize them to fulfil some of their services targets (15). This makes them over loaded.…”
Section: Discussionsupporting
confidence: 85%
“…There were six closed ended questions regarding NCDs, six questions regarding modifiable risk factors of common NCDs and five questions related to awareness or knowledge of NPCDCS program among health workers. Categorization was done on the basis of score (maximum-17) in three category, poor (0-6), fair (7)(8)(9)(10)(11)(12)(13)(14)(15) and good (more than 15). Strategy for collection -After taking approval from institutional ethics committee and written informed consent by participant, semi structured questionnaire for NCD & NPCDCS activities and In-depth interview were conducted to find out the constraints and their solution suggested by peripheral health workers to run NPCDCS program smoothly.…”
Section: Methodsmentioning
confidence: 99%
“…There was no vacant post of ANM at any subcentre in the present study which should be to reduce one of challenges faced by peripheral health worker in the field, where as Meena et al . [ 14 ] reported that over work loaded peripheral health workers faced issues to do their work efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Uneven population distribution also adds to increase in travel time. Studies have shown that the expansion of geographic areas for living due concomitant population growth have resulted in an increase of travel time across the country (Meena et al, 2020). Additionally, the study found that ASHAs’ time walking in the field has increased.…”
Section: Discussionmentioning
confidence: 99%